Parental social support and academic self-efficacy among senior high school students during preparation for SBMPTN - Bagita Nurmala; Yulia Fitriani (Program Studi bimbingan Konseling PPs UNM Makassar, 2021)
This study aims to explore the relationship between parental social support and academic self-efficacy among senior high school students who took cram schools to prepare for State University Joint Entrance Exams (SBMPTN). This was a correlational study with a quantitative approach. The population of the study was the high school students in the city of Bekasi who took cram schools to prepare for SBMPTN. The sample of this study was 100 students derived from the population using purposive sampling technique. The instruments of the study were the parental social support scale and the academic self-efficacy scale. Data were analyzed using correlation analysis technique. The results of the study showed there is a significant relationship between parental social support and academic self-efficacy with the r value 0.624 and the significance value 0.000 (p=0.01). The positive relationship indicates that the higher the parental social support, the higher students’ academic self-efficacy. On the contrary, the lower the parental social support, the lower students’ academic self-efficacy.